2016
DOI: 10.1016/j.talanta.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ultra-trace amounts of silver in water by differential pulse anodic stripping voltammetry using a new modified carbon paste electrode

Abstract: A highly sensitive and selective new procedure for the determination of silver in aqueous media was developed using a modified carbon paste electrode (MCPE) by differential pulse anodic stripping voltammetry (DPASV). The modified electrode was based on the incorporation of 2-hydroxybenzaldehyde benzoylhydrazone (2-HBBH) in the carbon paste electrode. Silver ions were preconcentrated on the modified electrode at open-circuit by complexation with the ligand and reduced to zero valent at a potential of 0V, and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…However, due to the lack of literature addressing this problem, it is difficult to establish a proper comparison. The results of the validation were in agreement with what has been published for methods determining silver in other systems (other working electrodes or modified electrodes) . In this work, Ag + was properly identified and the achievement of a single signal was possible.…”
Section: Discussionsupporting
confidence: 88%
“…However, due to the lack of literature addressing this problem, it is difficult to establish a proper comparison. The results of the validation were in agreement with what has been published for methods determining silver in other systems (other working electrodes or modified electrodes) . In this work, Ag + was properly identified and the achievement of a single signal was possible.…”
Section: Discussionsupporting
confidence: 88%
“…6 . By increasing the accumulation time for the second deposition step to 350 s, the detection limit, dened as DL ¼ 3Sb/m, 54 where Sb is the standard deviation of the blank (n ¼ 5) and m is the slope of the calibration curve, was found to be 0.02 mg L…”
Section: Analytical Performance Of the Double-stripping Voltammetry Mmentioning
confidence: 99%
“…Maximum contaminant level for total silver in drinking water, the US Environmental Protection Agency (EPA) fixed it as 0.1 mg/L -1 . It is also reported that the concentration of silver in water higher than 0.17 μg/L -1 is toxic to fish and microorganism [4,5]. The measurement and identification of ultra-trace levels in drinking water, water sources near factories and industries that released their waste into the rivers is very important [6].…”
Section: Introductionmentioning
confidence: 99%
“…The rapid methods involving bulk optode based on an ionophore [17], high sensitive and selective optical sensor [18], optical recognition [19] have used too. But electrochemical method is one of the most desirable methods for determination of silver because of its low cost, high sensitivity and simple preparation [5,20]. Cyclic voltammetry (CV), is very frequently used because it offers a wealth of experimental information and insights into both the kinetic and thermodynamic details of many chemical systems [21].…”
Section: Introductionmentioning
confidence: 99%